Video game programming for kids - Harbour, Jonathan S. (Boston, MA, USA : Course Technology, a part of Cengage Learning, 2013)
Requiring no prior programming experience, this book teaches kids introductory programming techniques with language that they can understand, using QB64, a simple, free version of BASIC. Includes quizzes and answers.
Includes index.
Keywords: Video games -- Design -- Juvenile literature